Innovation in Islamic Education Learning in the Digital Era to Address Multicultural Challenges - Sandrina Ramadhani; Sri Juwita; Donna Takrim; Abu Mansur; Baldi Anggara (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze innovation in Islamic education learning in the digital era in addressing multicultural challenges. This research employs a Systematic Literature Review (SLR) method based on the framework proposed by Barbara Kitchenham, consisting of planning, conducting, and reporting stages. Data were collected from relevant scientific publications indexed in Google Scholar, Scopus, and ScienceDirect, and analyzed using thematic analysis to identify patterns across studies. The findings indicate that innovation in Islamic education learning is primarily reflected in three aspects: the integration of digital technology, the application of innovative pedagogical models, and the adoption of student-centered learning approaches. At the same time, multicultural challenges include diverse student backgrounds, limited understanding of tolerance, and exposure to uncontrolled digital information. The study further reveals that the integration of digital innovation with multicultural values—through interactive learning media, project-based learning, and the strengthening of digital literacy—plays a significant role in fostering inclusive and tolerant attitudes among students. These findings highlight the importance of developing integrative curricula, enhancing teachers’ competencies, and promoting collaborative learning environments to support effective Islamic education in the digital era.